Large Scale Production of Silage with Probiotic Reinforcement of Lactococcus lactis IO-1 Recovered from L-lactic Acid Fermentation using Pre- Harvest Sago Palm (Metroxylon sagu) Frond - Muhammad Norhelmi, Ahmad (Universiti Malysia Sarawak, 2022)
The Sago palm industry is recognised as a major contributor to the food sector for the state of Sarawak. The efficiency of the sago palm to produce substantial amount of starch in minimal plantation area, resilience to grow under extreme conditions and adaptability towards climate change suggest that sago palm plantation needs to be acknowledged as the ideal crop to enable food security. However, the major restriction of sago palm plantation is the long maturation period for the sago to be harvestable for starch extraction is unfavourable for the expansion of sago plantation. Due to Malaysia's heavy reliance on imported food, particularly animal products, the country is currently experiencing a food crisis. To recover from the crisis, the level of livestock self-sufficiency must be raised. Unfortunately, Malaysia's livestock industry is heavily dependent on imported feed, and as a result, farmers and retailers are forced to absorb increased costs because the government has set a ceiling price for meat products. In order to make animal feed from pre-harvest sago palms, research was done to determine the potential of sago fronds as a low-cost, readily available alternative raw material. To increase the ensiling process, improve the silage's quality, and provide ruminants with a probiotic boost, Lactococcus lactis IO-1 is administered. Sago frond sap (SFSp) was extracted from sago rachis (200-230 mL/Kg) using a roller press machine then formulated as the substrate for the cultivation of Lactococcus lactis IO-1. The biomass was then recovered and used as the inoculant for silage production using mixtures of residual sago fibre (RSF) from the rachis and sago leaves (SL). Large scale production of inoculated (inoSFSil) and non-inoculated (conSFSil) silage was conducted to determine the effect of L. lactis IO-1 inoculation on the quality of the silage and growth performance of sheep via ad libitum feeding practice. Diluted (50%) SFSp generates the highest biomass of L. lactis IO-1 (14.53 g/L), associated with the highest productivity (0.98 g/L/hour) and concentration of L-lactic acid (24.02 g/L). The mixture of 1:1 RSF/SL was identified as the best formulation for silage production considering the five ideal characteristics (Dry Matter, Acid Detergent Fibre, Total Water Soluble Sugar, minimum pH and protein content). Amendment with L. lactis IO-1 definitely improves the efficiency of ensiling by accelerating the acidification process, hence refining the preservation of the protein content in the silage by 50%. Inoculation of L. lactis IO-1 ends up with silage containing high concentration of acetic acid (27.7 g/g), which maintains the viability of the LAB and improve aerobic stability of the silage to suppress secondary contamination from yeast and mould. The inoSFSil exhibit better feed efficiency with significantly lower residual feed intake (-125.35 g/day and 81.48 g/day) and feed conversion ratio (6.46 g/g and 12.93 g/g), respectively, compared to commercial pellet suggested inoSFSil was efficient for long term feeding. Meat obtained from animals fed with SFSil possessed higher water holding capacity helps to maintain structural integrity and ultimate pH to preserve the quality of the meat. The sensory evaluation shows that the texture of the SFSil fed meat corresponds to the commercial fed meat. Lack of fat content (5.3-8.4%) was not favourable to the chewiness of meat from animals fed with SFSil. Instead, it offers an option to the consumer as low-fat meat (<16%), which is recognised by the Malaysian Food Act and Regulation 1985 Regulation 141 (2). Therefore, utilization of sago frond from pre-harvest sago palm offers an effective substrate for the production of L-lactic acid and probiotics at once and provides a sustainable supply of animal feed from cheap and locally available raw material can simultaneously enhance the growth of sago and livestock industries in Sarawak.